2011
DOI: 10.1007/s00432-010-0973-x
|View full text |Cite
|
Sign up to set email alerts
|

Charlson Comorbidity Index is an independent prognostic factor among elderly patients with diffuse large B-cell lymphoma

Abstract: Among elderly DLBCL, high CCI was independently associated with worse outcome. Novel discrete strategies for these deteriorated patients are therefore warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 17 publications
5
43
2
2
Order By: Relevance
“…In a recent study, male sex, poor MNA, advanced disease stage, and poor mobility were found to be the 4 independent factors associated with early death (31) In this study, 44% of the patients received a full-dose regimen, 14% received reduced chemotherapy, and 42% received the best supportive care. A recent retrospective analysis conducted in elderly patients with DLBCL showed that high scores in the Charlson Comorbidity Index were an independent factor associated with low dose-intensity regimen and worse outcome, whereas age exceeding 80 years was not (78). So, while the best method for identifying nonfit patients is not known, it is important to use one of the available indices before treatment, and to include them in clinical trials in which patients more than 65 years of age are enrolled.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, male sex, poor MNA, advanced disease stage, and poor mobility were found to be the 4 independent factors associated with early death (31) In this study, 44% of the patients received a full-dose regimen, 14% received reduced chemotherapy, and 42% received the best supportive care. A recent retrospective analysis conducted in elderly patients with DLBCL showed that high scores in the Charlson Comorbidity Index were an independent factor associated with low dose-intensity regimen and worse outcome, whereas age exceeding 80 years was not (78). So, while the best method for identifying nonfit patients is not known, it is important to use one of the available indices before treatment, and to include them in clinical trials in which patients more than 65 years of age are enrolled.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that older patients with DLBCL may be treated with standard R-CHOP, the same as younger patients if their comorbid condition is tolerable (26). Recently, the entity of the RDI was proposed as an index of the intensity of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…1 The depth of hematologic response, in particular the achievement of complete hematologic response (CR), has been shown to be predictive of clinical response, quality of life and improvement in survival.…”
Section: Bortezomib and High-dose Melphalan Conditioning For Stem Celmentioning
confidence: 99%